1984
DOI: 10.1246/bcsj.57.1784
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron Angular Distribution and Assignment of Photoelectron Spectrum of Ozone

Abstract: For the first three ionized states of ozone the ordering of 2A1, 2B2 and 2A2 states has so far been controversial both experimentally and theoretically. The present work establishes assignment of the 2A2 state by using the characteristic of electron energy dependence of an asymmetry parameter (β) of photoelectron angular distribution measured with NeI, HeI, and NeII resonance radiation. From measurements of photoelectron spectra of ozone with NeI, HeI, and HeII radiation, we newly find that two bands centered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 21 publications
7
40
0
Order By: Relevance
“…The signal-tonoise ratio of our PI measurement would have been sufficiently high to observe a step in the PI spectrum corresponding to the first weak band observed at 12.44 eV by Dyke et al 12 and Katsumata, Shiromaru, and Kimura. 14 We attribute this apparent contradiction to the different temperatures of the O 3 sample and conclude that the first band observed in the HeI photoelectron spectra of room temperature O 3 represents a hot band, as already suggested by Müller, Köppel, and Cederbaum. 27 Three types of bands are observed in the PFI-ZEKE photoelectron spectrum.…”
Section: A Vibronic Structuresupporting
confidence: 56%
See 2 more Smart Citations
“…The signal-tonoise ratio of our PI measurement would have been sufficiently high to observe a step in the PI spectrum corresponding to the first weak band observed at 12.44 eV by Dyke et al 12 and Katsumata, Shiromaru, and Kimura. 14 We attribute this apparent contradiction to the different temperatures of the O 3 sample and conclude that the first band observed in the HeI photoelectron spectra of room temperature O 3 represents a hot band, as already suggested by Müller, Köppel, and Cederbaum. 27 Three types of bands are observed in the PFI-ZEKE photoelectron spectrum.…”
Section: A Vibronic Structuresupporting
confidence: 56%
“…In NO 2 , the crossing point is located in the near infrared (Ϸ10 000 cm Ϫ1 above the ground state͒ and leads to extensive perturbations of the vibronic structure in the entire visible spectrum. 8 The O 3 ϩ cation has been studied using conventional photoelectron spectroscopy, [10][11][12][13][14][15] photoionization mass spectrometry, 16,17 photofragment spectroscopy, 18 and electron impact ionization. 19 Already the early HeI photoelectron spectroscopic studies showed that the lowest three cationic electronic states 1 2 A 2 , 1 2 A 1 , and 1 2 B 2 are located within an energy interval of only about 1 eV ͑the lowest two states are almost degenerate and could not be resolved in the HeI spectra͒.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionization spectra of ozone have also been extensively studied both by experiments [12][13][14][15][16][17][18] and theories [4,6,9,[19][20][21][22][23][24][25][26][27]. The quasi-degeneracy in the ground state causes a breakdown of the Koopmans' picture.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, multireference theories are required for accurate descriptions of the ionized states. For example, a problem in the assignment of the first three peaks had been discussed for many years but seems to have been settled recently [4,6,9,15,22]. However, only qualitative assignments [14,19,20] were given for many correlation peaks that were observed in the higherenergy region of the He II photoelectron spectrum [15].…”
Section: Introductionmentioning
confidence: 99%